Substance Use Behavior among Early-Adolescent Asian American Girls: The Impact of Psychological and Family Factors - Fang, Lin (2011)
Confronting developmental tasks and challenges associated with bridging two different cultures, Asian American adolescent girls face increasing risks for substance use. Identifying risk and protective factors in this population is essential, particularly when those factors can inform preventive programs. Guided by family interaction theory, the present cross-sectional study explored the associations of psychological and familial factors with use of alcohol, prescription drugs, and other drugs among early-adolescent Asian American girls. Between August 2007 and March 2008, 135 pairs of Asian American girls (mean age 13.21 years, SD = 0.90) and their mothers (mean age 39.86 years, SD = 6.99) were recruited from 19 states that had significant Asian populations. Girls and mothers each completed an online survey. Relative to girls who did not use substances, girls who did had higher levels of depressive symptoms, perceived peer substance use, and maternal substance use. Multiple logistic regression modeling revealed that they also had significantly lower levels of body satisfaction, problem-solving ability, parental monitoring, mother-daughter communication, family involvement, and family rules about substance use. Household composition, acculturation, and academic achievement were not associated with girls’ substance use. These findings point to directions for substance abuse prevention programming among Asian American girls.